Identification of Key Conflict Nodes Based on Complex Network Theory. (August 2019) - Jiawei, Li; Xiangxi, Wen; Libiao, Zhang; Fei, Liu
Abstract: The current methods of detecting flight conflicts are difficult to grasp the overall conflict situation in the air, which is not conducive to the controllers to make accurate judgment on different conflict situations. In this paper, a method to identify key nodes of flight conflict based on complex network theory is proposed. Firstly, a conflict situation network model was built based on the ACAS protection area model. Then node degree centrality, closeness centrality and PageRank were used to evaluate the comprehensive importance of all nodes in the conflict situation network by AHP method. And we can find out the key conflict locations and conflict aircrafts based on the evaluation results of the index. The simulation results show that the model can effectively identify the key conflict aircrafts and positions in the airspace. And It can help controllers fully grasp the air security situation by classifing the air conflict situation levels.